INVESTIGATING THE ROLE OF AGRI-TECH STARTUP IN SUPPORTING INCLUSIVE FINANCE FOR FARMERS IN INDONESIA - Aziz, Subkhi Abdul; Prihadyanti, Dian; Sari, Karlina; Pitaloka, Ardanareswari Ayu (Universitas Padjadjaran, 2024)
Small-scale farmers are often financially excluded due to limited access to formal financial services. For decades, the Indonesian government has launched credit programs for farmers' financial inclusivity. However, it has yet to improve farmers' access to financial services significantly. The Indonesian government has encouraged financial technology providers to enhance credit financing for farmers. Besides fintech startups, agri-tech startup companies have helped provide digital financial services to the agricultural sector. This study aimed to analyze different types of agricultural startup businesses in supporting inclusive finance for farmers. This study uses a qualitative approach by conducting an online semi-structured interview as a data collection technique for four agri-tech startups and two experts. The data was analyzed by template analysis. The result showed that the presence of agri-tech startups could enhance farmers' opportunity to access new financial sources –either through crowdfunding or internal company financial resources - which is better than the existing financing schemes. However, several challenges arose regarding the existing culture that caused farmers to hesitate to join the agri-tech startups' program. Other challenges related to intermediaries' power in agricultural business that had strong ties with farmers' lives are the lack of infrastructure such as road and internet access and farmers' skill in using digital technology. Agri-tech startups have reduced those challenges by sending agriculture experts to the farmland, building intense communication with farmers, cooperating with intermediaries, and providing training for young farmers and farmer's children to optimize the use of smartphones in supplying agriculture knowledge and business.